Between UMNO and a hard place the Najib Razak era begins - Ooi, Kee Beng (Institute of Southeast Asian Studies Research for Social Advancement, 2010)
With a new coalition opposing him in parliament, Najib Razak has come to power wedged between his own coalition's aged traditions and the restive spirit of the times. Whether he can squeeze his way into a comfortable spot and stay in power is the question the coming years will answer.